Historical Rammed Earth Process Description Thanks to Micromorphological Analysis. Issue 3 (3rd April 2017) - Hamard, Erwan; Cammas, Cécilia; Fabbri, Antonin; Razakamanantsoa, Andry; Cazacliu, Bogdan; Morel, Jean-Claude
ABSTRACT: Rammed earth was traditionally used in western European countries before industrial building materials replace it during 20th century. Construction strategies developed by former builders were dictated by locally available construction materials and engendered local constructive cultures. Unfortunately, this knowledge was orally transmitted and is lost today. The rediscovery of these cultures can provide answers to modern rammed earth construction processes. Micromorphological analysis of earth walls provides information to rediscover traditional rammed earth process. This methodology is applied for the first time, on a rammed earth wall of a farm located in Bresse (France). Thanks to this methodology, pedological horizon, extraction depth, and location of the material source are identified. The surface area excavated for the construction of the building is estimated. Micromorphological study gives information on mixing degree and water content at implementation time. Strain features associated with ramming effect and rammed earth boundary layer are also highlighted.